KERAGAMAN JENIS DAN POPULASI MIKORIZA ARBUSKULA DALAM BERBAGAI KELOMPOK UMUR PINUS TUMPANGSARI KOPI DI UB FOREST - Achmad Jauhar Arifin; Budi Prasetya; Syahrul Kurniawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Differences in tree age and cropping systems may influence the microbial diversity, including fungal species and population. The purpose of this study was to determine the diversity, of species and population of arbuscular mycorrhiza spores and the relationship between the number of arbuscular mycorrhiza spores and the soil chemical properties in different pine age group and coffee as an intercropping system at sloped areas. The study was conducted from April to July 2017. The study used a survey method with 5 age groups (KU) and three replications. The study was divided into 3 stages: 1). collection of soil and root samples, as well as measuring plot characteristics (i.e. basal area, canopy cover, standing litter mass); 2). Measurement of Mycorrhizal in the laboratory (spore extraction, spore identification, root colony percentage analysis); 3). Soil Chemical Analysis (pH, total P, available P). All data was tabulated, and tested using ANOVA with Randomized Block Design. If there is a significantly different, a further LSD test is performed with a level of 5%. Correlation and regression tests were performed to determine the relationship between parameters. The results showed that there were significant differences in the parameters of canopy density, number of genus spores of Acaulospora 100 g-1 soil, Soil pH, and total P in the soil. However, the study was unable to detect significant differences in, other parameters, such as root infection, number population of Glomus and Gigaspore, available P, etc.. The correlation test showed that the increase in the age group of the coffee intercropping system did not correlate with the number of arbuscular mycorrhizae in each plot observed. The number of Arbuscular Mycorrhizal Spores in each age group of intercropping pine did not correlate with the soil's chemical properties (pH, P-Total, P-Available).